Proceedings of the Ocean Drilling Program, 148 Scientific Results 1996
DOI: 10.2973/odp.proc.sr.148.106.1996
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Crystallization Temperatures of Primary Melts from Hole 896A Basalts: Evidence from Melt Inclusion Studies

Abstract: Glass and mineral geochemical data are presented for basalts from Ocean Drilling Program (ODP) Hole 896A. Phenocryst assemblages are dominated by calcic plagioclase (An 76 _ 945 ) with olivine (Fo 80 _ 91 6 ), Cr-Al spinel, and clinopyroxene. The origin of the calcic plagioclase phenocrysts was investigated by heating-stage experiments on silicate melt inclusions in plagioclase and olivine mineral separates. Trapping temperatures of 1195°-1215°C are inferred for plagioclase (An 83 _ 945 ). Inclusion compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…The criteria outlined above are satisfied by MORB samples from ODP Hole 896A (McNeill and Danyushevsky, 1996). Samples from this hole underwent no plagioclase accumulation (Fig.…”
Section: Some Examples Of Poorly Understood Reequilibration Processesmentioning
confidence: 83%
See 3 more Smart Citations
“…The criteria outlined above are satisfied by MORB samples from ODP Hole 896A (McNeill and Danyushevsky, 1996). Samples from this hole underwent no plagioclase accumulation (Fig.…”
Section: Some Examples Of Poorly Understood Reequilibration Processesmentioning
confidence: 83%
“…8. Compositions of pillow-rim glasses from ODP Hole 896A (McNeill and Danyushevsky, 1996). Glasses from samples used in the melt inclusion study are identified on the lower plot.…”
Section: Some Examples Of Poorly Understood Reequilibration Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…Half of these samples come from a section of the Mid-Atlantic Ridge that was affected by Azores magmatism (enriched MORB samples in Table 2 of Green et al [2001]), and these are not representative of normal MORB [e.g., Langmuir et al, 1992]. Two samples with high FeO contents from Ocean Drilling Prograpm Site 896, east of the both the Galapagos archipelago and the Galapagos Rift, contain olivines with Fo 91.6 [McNeill and Danyushevsky, 1996]; these are samples 148-896A-27R-1,15 and 148-896A-3R-1,4 and, although they might have been influenced by the Galapagos plume, we initially consider these as NMORB. Two other samples come from a normal ridge.…”
Section: Morbmentioning
confidence: 99%